THE INFLUENCE OF LIFESTYLE AND MARKETING STIMULI ON PURCHASE DECISION OF BBQ HOME SERVICE IN MANADO - Monintja, Billy Theofany; Saerang, David P.E; Tumewu, Ferdinand J (Universitas Sam Ratulangi, 2024)
Online food delivery is the process concerned with the ordering of food products from the digital platform and management of the customer's orders. To market their products, online businesses should pay attention to some factors that can influence the purchase decision. The purpose of this study is to know the simultaneous and partial influence of lifestyle and marketing stimuli on purchase decision of BBQ home service in Manado. This research used multiple regression analysis with sample of 100 respondents. The result shows that lifestyle and marketing stimuli have a simultaneous and significant influence on purchase decision of BBQ home service in Manado simultaneously and partially. The BBQ Home Service should learn about the consumer’s wants and perception. The BBQ home service in Manado can take an advantage of consumer lifestyle in a good way to increase sales. Looking by Manado citizen lifestyle, the BBQ home service can add like a family menu or birthday party menu to attract the consumers Keywords: Lifestyle, Marketing Stimuli, Consumer Purchase Decision